"I felt there was a big chunk taken out of my life": COVID-19 and older adults' library-based magazine leisure reading. Issue 1 (2nd January 2023) - Dalmer, Nicole K.; Sawchuk, Dana; Ly, Mina
ABSTRACT: Reading is a central leisure activity among older adults, serving as a means of entertainment, escape, connection, and/or education. COVID-19 public library closures drastically altered this activity. Based on interviews with 21 older adults across Ontario, Canada, this study explores how library closures in the province affected older adults' magazine leisure reading practices. Analysis yielded three themes: COVID-19 transforming experiences of library as place, COVID-19 as time of loss, and COVID-19 as catalyst for adaptation. Participants voiced the many ways COVID-19 has shaped (often restricting) their choices related to magazine reading (where, how, and what they read, and where they located their magazines). While libraries remained virtually open during the pandemic, many participants chose not to switch to digital platforms (despite their technical proficiency to do so). As a result, they often stopped reading magazines completely, despite the loss this stoppage represented. At the same time, pandemic restrictions compelled others to use the online library services they had previously avoided. Ultimately, participants' experiences of magazine reading during the COVID-19 pandemic further our understanding of reading as leisure in later life and also trouble prevailing assumptions that older adults' resistance to digital media engagement is merely a reflection of age-related incompetence.